2020
DOI: 10.1007/s10067-020-05121-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term results of single-dose intra-articular peptide with hyaluronic acid and platelet-rich plasma injections in knee osteoarthritis: a randomized study

Abstract: Introduction/objectives Intra-articular injections may be useful in terms of pain and functional status, in knee osteoarthritis (OA). Besides hyaluronic acid (HA) and platelet-rich plasma (PRP), peptide molecules recently begin to be used. The aim of this study was to compare the efficacy of intra-articular peptide Prostrolane® (CAREGEN Co. Ltd.) injection with that of the HA and PRP in the persons with OA. Method Fifty-four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Platelet-rich plasma is beginning to replace the more common injectable therapies of intra-articular corticosteroids and hyaluronic acid. New evidences suggest pain relief and functional improvement were obtained after the intra-articular hyaluronic acid, peptide and platelet-rich plasma injections in osteoarthritis, and decrease in pain was better in the peptide group [34]. Small studies have examined prolotherapy and stem cell therapy, and demonstrate some benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma is beginning to replace the more common injectable therapies of intra-articular corticosteroids and hyaluronic acid. New evidences suggest pain relief and functional improvement were obtained after the intra-articular hyaluronic acid, peptide and platelet-rich plasma injections in osteoarthritis, and decrease in pain was better in the peptide group [34]. Small studies have examined prolotherapy and stem cell therapy, and demonstrate some benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many high-quality RCTs were excluded because of the stringent inclusion criteria, and the feasibility of the articles depends on the methodological quality of the included articles. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…In total, this systematic review included data from 2705 subjects (1298 in the PRP arm and 1407 in the control arm). The included studies were published between 2012 [21] and 2020 [22][23][24][25][26]. Participants enrolled in the selected studies included individuals diagnosed exclusively with knee OA.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Participants enrolled in the selected studies included individuals diagnosed exclusively with knee OA. The participants' follow-up varied among the studies from 3 months [25,27] to 2 years [28]. The trials reported the use of different PRP formulations; six studies did not report sufficient information about the PRP used [27,[29][30][31][32][33], and they could not be classified.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation